PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA INSTANSI PEMERINTAH DAERAH STUDI KASUS DINAS PERTANIAN DAN PERTERNAKAN KABUPATEN MUSI BANYUASIN - Hendry Wijaya (Jurnal Media Ekonomi (JURMEK), 2016)
In this study there are two variables that will go through the processing and discussion of data so that conclusions can be drawn, the two variables are Employee Discipline (independent variable) and Employee Performance (dependent variable). This study aims to determine how much influence the discipline on the performance of employees in the local government agencies of Musi Banyuasin Regency (case study of the Department of Agriculture and Animal Husbandry in Musi Banyuasin Regency). Banyuasin. This study uses primary and secondary data. The analysis technique of this study uses quantitative methods which use statistical equations in processing and discussing data obtained from respondents through media questionnaires. The results of this study indicate that there is an influence between employee discipline and employee performance with magnitude the score of the effect of the regression test results is 0.178.